2021
DOI: 10.7759/cureus.15849
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of High-Resolution Computed Tomography Scan in COVID-19: Do We Need to Think Outside the Box?

Abstract: Background and objectiveThe ambiguous nature and high infectivity of the coronavirus disease 2019 (COVID-19) have caused soaring morbidity and mortality worldwide. Real-time polymerase chain reaction (RT-PCR) is preferred for detecting COVID-19. However, its poor sensitivity and the emerging use of high-resolution CT (HRCT) scan for disease severity make the use of RT-PCR quite obsolete. In light of this, our study aimed to explore the beneficial role of HRCT and compare the HRCT findings across various patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…The mean age in the current study was 51.69 ± 16.02 years, and most of the study participants were male. In comparison to the current study, Khan et al [ 15 ] found the mean age of the patients as 54.0 ± 14.0 years (range: 24-83 years). All the laboratory parameters like mean ferritin level, LDH levels, erythrocyte sedimentation rate, D-dimer, interleukin-6, and neutrophil-to-lymphocyte ratio were highly altered in the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…The mean age in the current study was 51.69 ± 16.02 years, and most of the study participants were male. In comparison to the current study, Khan et al [ 15 ] found the mean age of the patients as 54.0 ± 14.0 years (range: 24-83 years). All the laboratory parameters like mean ferritin level, LDH levels, erythrocyte sedimentation rate, D-dimer, interleukin-6, and neutrophil-to-lymphocyte ratio were highly altered in the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…This feature was reported in a recent study mentioning that the posterior basal segment of the right lower lobe was relatively more affected than the left (89.7% vs 64.2%). Adding further, apical (67.9% vs 46.2%), anterior (59.7% vs 48.7%) and posterior (85.9% vs 66.7%) of the upper lobe were more affected in the right side compared to the left [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may begin early with reticular changes in the lungs but soon this progress to ground-glass opacities, crazy paving pattern, lobar and segmental involvement, mediastinal lymph node swelling and extra-pulmonary manifestations such as pericardial effusion [ 14 ]. However, the only drawback HRCT has is that the imaging modality is not as widely available in developing countries and depending on it for the final diagnosis leads to a lot of burden on healthcare [ 15 , 16 ]. Every single scan takes a certain amount of time and it cannot be as robust and quick as a chest X-ray (CXR).…”
Section: Introductionmentioning
confidence: 99%